Age, Education, and Gender in Employment: A Case Study of Butwal Sub-Metropolitan City, Nepal - Devkota, Chiranjivi (Rural Development Journal, 2025)
This paper analyzes the impact of age, education level and gender on the employment status of the people residing in the Butwal Sub-Metropolitan City, especially the elements defining access towards formal employment. The study shows that employment status in the population depends on age, level of education, and gender. Overall, young people who got employed in the formal sector were aged less than 40, with education levels of 12 and above. Gender inequalities are still evident, in particular, man-dominance in the employment of the better-off and more secure sectors because of social injustices that have always confined women to low-paying roles. It was also ascertained that age by education has a synergistic effect on employment with the workers that are young with advanced education enjoying better employment prospects. The results call for strong policy intervention concerning the enhancement of educational participation and attainment, formal gender equality, and affirmative action for the employment of younger persons. Attention should be paid to eradicating gender discrimination as well as improving the rights of both males and females in the education sector together with providing suitable conditions for older employees. In conclusion, the study asserts that eliminating these demographic imbalances will demand concerted efforts in terms of education policy and gender mainstreaming, employment initiatives for women and youth and policies that support equal participation of the demography in the labour market.